INDIVIDUALITY AND SOCIAL INTERESTS IN AHMAD FUADI'S 'ANAK RANTAU': AN INDIVIDUAL PSYCHOLOGICAL CRITICISM - Wildana Wargadinata; Arina Haque; Iffat Maimunah; Apri Wardana Ritonga (Leksema: Jurnal Bahasa dan Sastra, 2021)
This study aims to know and analyze the theory of individuality and social interest based on Alfred Adler's perspective on the main character in the novel Anak Rantau written by Ahmad Fuadi. The approach in question is related to the personality psychology of the main character, which is known from the storyline. The method used in this research is descriptive-qualitative based on literature review. The result of this research is that the main character in the novel reflects the theoretical principles in their attitudes, behavior, decisions, and speech acts. The individuality of the main character can be seen from the awareness of his past attitudes, his characteristics that are not easily afraid, and his efforts to compensate for his inferiority. Meanwhile, the social interests of the main character develop in line with the long process in the village community.